The frequency of non-motor symptoms in SCA3 and their association with disease severity and lifestyle factors - Hengel, Holger; Martus, Peter; Faber, Jennifer; Giunti, Paola; Garcia-Moreno, Hector; Solanky, Nita; Klockgether, Thomas; Reetz, Kathrin; van de Warrenburg, Bart P.; Santana, Magda M.; Silva, Patrick; Cunha, Inês; et al. (Journal of neurology, 2022)
Non-motor symptoms (NMS) are a substantial burden for patients with SCA3. There are limited data on their frequency, and their relation with disease severity and activities of daily living is not clear. In addition, lifestyle may either influence or be affected by the occurrence of NMS.